2023
DOI: 10.3847/1538-3881/acd935
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Spectroscopy of the Lowest-density Gas Giant: Metals and a Potential Extended Outflow in HAT-P-67b

Abstract: Extremely low-density exoplanets are tantalizing targets for atmospheric characterization because of their promisingly large signals in transmission spectroscopy. We present the first analysis of the atmosphere of the lowest-density gas giant currently known, HAT-P-67b. This inflated Saturn-mass exoplanet sits at the boundary between hot and ultrahot gas giants, where thermal dissociation of molecules begins to dominate atmospheric composition. We observed a transit of HAT-P-67b at high spectral resolution wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Recently, Bello-Arufe et al (2023) reported the transmission spectrum of HAT-P-67 b using the CARMENES spectrograph (Quirrenbach et al 2014). The point-and-stare observations were scheduled to coincide with transits, providing relatively short <1 hr out-of-transit baselines on either side of the transit.…”
Section: Comparison To Carmenes Detectionmentioning
confidence: 99%
“…Recently, Bello-Arufe et al (2023) reported the transmission spectrum of HAT-P-67 b using the CARMENES spectrograph (Quirrenbach et al 2014). The point-and-stare observations were scheduled to coincide with transits, providing relatively short <1 hr out-of-transit baselines on either side of the transit.…”
Section: Comparison To Carmenes Detectionmentioning
confidence: 99%